Evaluation of therapeutic management in women with lumbar spine pain complaints - Agnieszka Zbylut; Katarzyna Wódka (University of Applied Sciences in Tarnow, Poland, 2023)
Aim of the study: To evaluate the effects of two different modes of improvement on the level of perceived pain, spinal mobility, lumbar spinal motion control and limitations in activities of daily living in women aged 51-62 with lumbar spine pain. Material and methods: The study included a group of 31 women between the ages of 51 and 62. The subjects were divided into 2 groups. Group I (FK) received physical therapy treatments and general gymnastics, while group II (FS) received physical therapy treatments and exercises using a PBU stabilizer. The project covered a period of 10 treatment days excluding Saturdays and Sundays. Before and immediately after the rehabilitation, tests of flexion and extension control in the L-spine, active knee joint flexion test, Schober test were performed, and the NRS scale was used scale and QBPDS scale. Results: After the applied rehabilitation, a significant reduction in the level of perceived pain and improvement in spinal mobility in the direction of flexion were observed in both groups. In the FS group, there was also a significant improvement in lumbar flexion control and better lumbar spine control during the active knee flexion test. In addition, a reduction in disability as measured by the QBPDS scale was noted. Conclusions: The use of comprehensive rehabilitation brings significant improvements in terms of pain reduction and improvement in lumbar spine mobility in the flexion direction. A two-week exercise program using a stabilizer appears to yield significantly better results in terms of lumbar flexion control as well as better lumbar control during the active flexion test of both knee joints. And this, in turn, may affect the results obtained using the QBPDS scale among FS subjects.